Daily field checking list by Walter Rosene, March 30, 1941 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed at Dunbar Slough by Walter Rosene and Robert Walker, March 30, 1941. Plustek--flatbed